Modified Mediterranean-ketogenic diet modulates gut microbiome and short-chain fatty acids in association with Alzheimer's disease markers in subjects with mild cognitive impairment - Nagpal, Ravinder; Neth, Bryan J.; Wang, Shaohua; Craft, Suzanne; Yadav, Hariom (EBioMedicine, 2019)
Alzheimer's disease (AD) prevalence is increasing, but its etiology remains elusive. Gut microbes can contribute to AD pathology and may help identifying novel markers and therapies against AD. Herein, we examine how the gut microbiome differs in older adults with mild cognitive impairment compared to cognitively normal counterparts, and whether and how a modified Mediterranean-ketogenic diet (MMKD) alters the gut microbiome signature in association with cerebrospinal fluid (CSF) AD biomarkers. A randomized, double-blind, cross-over, single-center pilot study of MMKD versus American Heart Association Diet (AHAD) intervention is performed on 17 subjects (age: 64.6 ± 6.4 yr), of which 11 have mild cognitive impairment, while 6 are cognitively normal. Subjects undergo MMKD and AHAD intervention for 6-weeks separated by 6-weeks washout periods. Gut microbiome, fecal short-chain fatty acids (SCFAs), and markers of AD in CSF including amyloid β (Aβ)-40 and Aß-42, total tau, and phosphorylated tau-181 (tau-p181) are measured at before and after diet interventions. At baseline, subjects with normal vs. impaired cognition show no notable difference in microbiome diversity but several unique microbial signatures are detected in subjects with mild cognitive impairment. Proteobacteria correlate positively with Aβ-42: Aβ-40 while fecal propionate and butyrate correlates negatively with Aβ-42 in subjects with mild cognitive impairment. Several bacteria are differently affected by the two diets with distinct patterns between cognitively normal and impaired subjects. Notably, the abundance of Enterobacteriaceae, Akkermansia, Slackia, Christensenellaceae and Erysipelotriaceae increases while that of Bifidobacterium and Lachnobacterium reduces on MMKD, while AHAD increases Mollicutes. MMKD slightly reduces fecal lactate and acetate while increasing propionate and butyrate. Conversely, AHAD increases acetate and propionate while reducing butyrate. The data suggest that specific gut microbial signatures may depict the mild cognitive impairment and that the MMKD can modulate the gut microbiome and metabolites in association with improved AD biomarkers in CSF.